2006
DOI: 10.1111/j.1365-2788.2006.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and mortality in persons with Down’s syndrome

Abstract: Our study is one of the largest population-based studies to date. We found that despite the exponential increase in prevalence with age, the prevalence of dementia in the oldest persons with DS was not higher than 25.6%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
183
3
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(199 citation statements)
references
References 38 publications
4
183
3
9
Order By: Relevance
“…1). Thus, as with AD in the general population, age is a strong independent risk factor for AD-DS 21 . By the age of 65, 68-80% of individuals with DS have been shown to have developed dementia 6,7 (FIG.…”
Section: Prevalence Of Ad-dsmentioning
confidence: 88%
See 2 more Smart Citations
“…1). Thus, as with AD in the general population, age is a strong independent risk factor for AD-DS 21 . By the age of 65, 68-80% of individuals with DS have been shown to have developed dementia 6,7 (FIG.…”
Section: Prevalence Of Ad-dsmentioning
confidence: 88%
“…The average age at which menopause begins in women with DS correlates with the age of onset of dementia 24-26 ; however, unlike the incidence of AD in euploid individuals, gender does not affect the incidence of AD-DS 20,21 . The reasons for this difference between the two populations are unknown, although it is possible that trisomy may cause changes in hormonal or cardiovascular biology that alter AD risk.…”
Section: Prevalence Of Ad-dsmentioning
confidence: 99%
See 1 more Smart Citation
“…in sizes of the prefrontal cortex, cerebellum, hippocampus, amygdala, and brain stem in newborn individuals with DS (Aylward et al, 1997;Dierssen, 2012;Guidi et al, 2008), and structural abnormalities such as reduced dendritic and axonal number and volume, and altered synaptic plasticity (L. Becker, Mito, Takashima, & Onodera, 1991;Coppus et al, 2006;Dierssen, 2012). These brain deficits in individuals with DS are associated with cognitive and intellectual deficits including memory deficiencies, and motor dysfunction.…”
Section: Individuals With Ds Display Developmental Alterations In Bramentioning
confidence: 99%
“…The actual rate of conversion varies among studies, but the most recent data on 506 individuals with DS (ages show the highest prevalence of dementia is 32.1% in the age group 55-59; the rate is 17.7% in 50-54 year olds and 8.9% in 45-49 year olds (Coppus, Evenhuis et al 2006). We conducted a prospective study using PET and MRI starting with middle-aged persons with DS, none of whom showed clinical signs of dementia when they entered the study.…”
mentioning
confidence: 99%